Groundwater Pollution Prevention and Control: Current Status and Countermeasures - Ren Jing; Li Juan; Xi Beidou; Yang Yang; Lu Haojie; Shi Junxiang (中国工程科学, 2022)
Groundwater is a significant source of drinking water and a strategic resource for China. However, the groundwater quality in China is unoptimistic and China faces a severe situation regarding groundwater environment protection as its groundwater pollution prevention and control started late. Therefore, problems faced by groundwater pollution prevention and control should be researched and targeted countermeasures be proposed to curb the trend of groundwater pollution and improve groundwater quality. The study reviews the existing regulations and policies, management status, and requirements of groundwater pollution prevention and control in China, and predicts the future management trend. The results indicate the following challenges. (1) The groundwater pollution status is still unclear and hierarchical and classified management of groundwater pollution is lacking. (2) The groundwater pollution forms become increasingly complex and the regulatory system requires improvement. (3) The groundwater pollution control becomes increasingly difficult and only few control technologies were applied to underground pollution treatment. (4) The requirements of groundwater environmental management are constantly improving; however, the innovation impetus is insufficient. Therefore, we proposed several countermeasures. The pollution status should be identified through continuous investigation and assessment of groundwater environment in key regions, to support the construction of a hierarchical and classified management system. Intelligent, visualized, and coordinated supervision should be achieved by establishing a multilevel groundwater environmental monitoring network and adopting supervisory measures based on information technologies. Green and sustainable models should be formed and promoted through the experimental implementation of groundwater pollution prevention and control projects and by constructing 21 pilot sites. The original innovation and management capacities should be enhanced by focusing on key technical issues such as groundwater pollution traceability, standards system construction, and development of relevant software with proprietary intellectual property rights.